Aortic aneurysm evaluation by scanning acoustic microscopy and Raman spectroscopy - Tanören, Bukem; Parlatan, Uğur; Parlak, Melita; Keçoğlu, İbrahim; Burçin Ünlü, Mehmet; Öztaş, Didem Melis; Ulukan, Mustafa Özer; Erkanlı, Korhan; Uğurlucan, Murat (Royal Society of Chemistry, 2021)
Aortic aneurysm is observed as a result of the extensive alteration in the elasticity of the aortic wall due to the breakdown of elastin and collagen. In this study, we studied the feasibility of scanning acoustic microscopy (SAM) and Raman spectroscopy (RS) in characterizing the dilated segments of the aorta from male and female patients with aortic aneurysm. SAM determined the acoustic property variation in the aorta by calculating the acoustic impedance values of aorta samples of 18 patients. RS determined the disease states by analyzing the chemical variation especially in the peaks related to elastin and collagen using the k-means classification method. Consequently, we assume that combining these two techniques in clinics will help to investigate the dilated segment of the aorta with micrometer resolution, which will reduce the possibility of new aneurysm formation due to a segment not excised during the surgery.
Keywords: Raman Spectroscopy; Acoustic Microscopy; Aortic Aneurysm